DESAIN SISTEM INFORMASI DAN LAPORAN KEUANGAN PADA ORGANISASI NIRLABA - Mardiana Andarwati (Jurnal Teknologi dan Manajemen Informatika, 2016)
A nonprofit information system for recording transactions of non-profit organizations cash receipts, cash disbursements, buying, selling of products/ services, depreciation does not exist the difference with the business organizations. But what makes the difference is the party be the owner, until no transactions related to sales a change of ownership or allocation of funds/resources from liquidation. If The non-profit organizations to generate profits, no transaction is used for distribution of profits to the founder or owner. Given the non-profit organizations need financial statements to provide relevant information and to meet the interests of the donors, the organization's members, creditors, and other parties provide resources for nonprofit organizations. DOI: https://doi.org/10.26905/jtmi.v2i1.619